Sadruşşerîa es-Sânî ve tasavvuf anlayışı - Dumlu, Zeyneb (My University, 2023)
Sadruşşerîa es-Sânî (ö. 747/ 1346) Hanefi fakihi ve mütekellim olmasının yanı sıra tefsir, hadis, belagat, felsefe gibi alanlarda yetkin olan, eserleri Osmanlı medreselerinde ders kitabı olarak okutulan bir âlimdir. Bu çalışmada bu güne kadar zikri geçen ilimlere dair eserleri üzerinde durulan fakat Mâverâünnehir’de ulemâ-sûfî birlikteliğinin bir halkası olarak sûfi kimliğine atıf yapılmayan Sadruşşerîa’nın tasavvufî muhitlerle ve şeyhi Hasan Bulgârî ile irtibatı, tasavvufî perspektiften kaleme aldığı “Makâmâtü'l-ârifin” ve “Te’vîl-i Kıssa-i Yûsuf” adlı eserlerinden hareketle tasavvuf anlayışı ortaya konacaktır.

Sadr al-Shariah al-Thanî (747/ 1346) was a scholar who was competent in fields such as tafsir, hadith, rhetoric, and philosophy, as well as being a Hanafi jurist and mutakallim, whose works were taught as textbooks in Ottoman madrasahs. In this study, Sadr al-Shariah's contact with the Sufi connexion and his sheikh Hasan Bulgârî, whose works on the sciences mentioned so far are emphasized as a link of the ulema-sufi unity in Transoxiana, and whose sufi identity is not referenced, is reflected in his works Makâmâtü'l-ârifin and Te'vîl-i Kıssa-i Yûsuf (Interpretation of Yusuf’s Parable), which he wrote from a sufi perspective. The understanding of sufism will be revealed through this movement.
Sadr al-Shariah al-Thanî and his understanding of sufism
Keywords: Makâmâtü’l-arifîn; Sadruşşerîa; Sûfi; Sufism; Tasavvuf; Te’vîl-i Kıssa-i Yûsuf; Te’vîl-i Kıssa-i Yûsuf Sadr al-Shariah